2016
DOI: 10.1007/s00429-016-1278-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the connectivity of serotonin transporter immunoreactive axons to excitatory and inhibitory neurochemical synapses in the mouse limbic brain

Abstract: Serotonin neurons arise from the brainstem raphe nuclei and send their projections throughout the brain to release 5-HT which acts as a modulator of several neuronal populations. Previous electron microscopy studies in rats have morphologically determined the distribution of 5-HT release sites (boutons) in certain brain regions and have shown that 5-HT containing boutons form synaptic contacts that are either symmetric or asymmetric. In addition, 5-HT boutons can form synaptic triads with the pre- and postsyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 88 publications
4
38
1
Order By: Relevance
“…This suggests a potential role of cortical 5-HT in the regulation of neurotransmitter release. In line with this, we showed that 5-HT boutons essentially form synaptic triads with excitatory synapses in the upper layer of the mouse prefrontal cortex and were located closer to the presynaptic than the postsynaptic specializations, also suggesting a role of 5-HT in the regulation of excitatory neurotransmitter (glutamate) release 13 . The potential role of 5-HT in the regulation of excitatory transmission has been demonstrated in electrophysiology studies showing a 5-HT-mediated increase in glutamate release and amplitude of glutamatergic EPSCs at the apical dendrites of pyramidal neurons 19 .…”
Section: Cortexsupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests a potential role of cortical 5-HT in the regulation of neurotransmitter release. In line with this, we showed that 5-HT boutons essentially form synaptic triads with excitatory synapses in the upper layer of the mouse prefrontal cortex and were located closer to the presynaptic than the postsynaptic specializations, also suggesting a role of 5-HT in the regulation of excitatory neurotransmitter (glutamate) release 13 . The potential role of 5-HT in the regulation of excitatory transmission has been demonstrated in electrophysiology studies showing a 5-HT-mediated increase in glutamate release and amplitude of glutamatergic EPSCs at the apical dendrites of pyramidal neurons 19 .…”
Section: Cortexsupporting
confidence: 80%
“…Therefore, we have recently developed a semi-quantitative method combining high-resolution confocal microscopy and 3D reconstruction of 5-HT transporter SERT-positive axons to map the distribution of 5-HT boutons apposed to either excitatory or inhibitory neurochemical synapses in the mouse limbic brain 13 . Briefly, we labeled serotonin transporter (SERT) immunoreactive axons and reconstruct in 3D their distribution within limbic brain regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were deconvolved using Huygens Professional v16.10 (Scientific Volume Imaging) with 100 iterations, quality threshold at 0.001, signal to noise ratio at 15 for the three channels. Images were subsequently analysed in Imaris 8.2.1 (Bitplane), as previously described ( Belmer et al, 2017 ). Total YFP punctate fluorescence (α4-YFP) ( Figure 1A ) was quantified using the spot detection function of Imaris, with a spot diameter of 0.4 μm ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%
“…Since Syn, the molecular marker for presynaptic vesicle membrane, can be used for quantitative estimation of synaptic formation (Belmer et al, 2016), the finding that about 16% of the 5-HTergic varicosities densely distributed in layer V of mPFC expressed Syn suggests an equivalent fraction of 5-HT swellings may possibly engage in putative synaptic construct in the same region. This ratio is comparable with that of an EM study showing that about 19% of the total 5-HT varicosities in laminae V-VI of ventral mPFC formed synapses (Miner et al, 2000).…”
Section: Functional Significance Of the Contacts Between 5-htergic Fimentioning
confidence: 99%